Both coronary arteries originating from the pulmonary artery: A case report [Her iki koroner arterin pulmoner arterden köken almasi: Bir vaka takdimi] - (:unkn) unknown (My University, 2009)
Both coronary arteries originating from the pulmonary artery is an extremely rare potentially fatal condition reported in only a few cases, causing dilated cardiomyopathy in early infancy. We report a three-month-old patient presenting with cardiomegaly and heart failure accompanied by echocardiographic findings of dilated cardiomyopathy and both coronary arteries originating from the pulmonary artery.
Keywords: ALCAPA; Coronary artery abnormality; Dilated cardiomyopathy